Lévi-Strauss et les deux Amériques II- L’Amérique du Nord, ou l’adieu au primitivisme - Emmanuel Désveaux (Nuevo mundo - Mundos Nuevos, 2017)
At the beginning of the 1950s, following the publication of Les Structures élémentaires de la parenté, Lévi-Strauss tried to give a second impulse to his research. The ethnographical corpus dedicated to the North American Indians thus played a crucial role in this phase of his intellectual story, allowing him to define the method of analysis of the myths that he will display in Les Mythologiques.  A new degree of ethnographical complexity imposes itself upon him; the consequence will be the renunciation of the primitivist paradigm which haunted him until then